Hubungan Perceived Severity Dengan Perilaku BABS Pada Masyarakat Pesisir kab. Takalar Tahun 2024 - Muhammad Ikhtiar; Kanaya Alifia Riswan; Andi Asrina; Ayu Puspitasari (Direktorat Politeknik Kesehatan Makassar, 2024)
The 2010 Riskesdas results show that 24.7% of the population defecates in open areas and 11.7% defecates in holes in the ground. Meanwhile, access to sanitation includes ownership/use of toilets, type of toilet and final disposal of feces at 55.5%. The aim of this research was to determine the relationship between Perceived Severity and defecation behavior. The research method used was quantitative, cross sectional study design, the sampling technique used probability sampling with a simple random sampling approach, the number of research respondents was 161 respondents. Data collection was carried out by interviews and observations. The data analysis method was carried out using bivariate tests and Chi-Square correlation tests. The research results show that the perceived severity variable is related to defecation behavior, this is indicated by a maximum of 72.7% positive statements, this is because people realize that defecating in the river is wrong behavior, defecating in the river will also make the surrounding environment polluted and mixed with feces. Humans contain many disease-causing germs. The results of the chi-square test analysis show P Value = 0.000, which means there is a relationship. The conclusion in the research is that there is a relationship between Perceived Severity and Open Defecation behavior in the Coastal Community of Takalar Regency where all respondents based on perceived severity (vulnerability) show that they have sufficient perception. Keywords: Perceived, Severity, Coastal Community